The Clinical Value of Procalcitonin in the Neutropenic Period After Allogeneic Hematopoietic Stem Cell Transplantation - Shan, Meng; Shen, Danya; Song, Tiemei; Xu, Wenyan; Qiu, Huiying; Chen, Suning; Han, Yue; Tang, Xiaowen; Miao, Miao; Sun, Aining; Wu, Depei; Xu, Yang (Frontiers in Immunology, 2022)
The diagnostic value of procalcitonin and the prognostic role of PCT clearance remain unclear in neutropenic period after allogeneic hematopoietic stem cell transplantation Introduction. This study evaluated 219 febrile neutropenic patients (116, retrospectively; 103, prospectively) who underwent allo-HSCT from April 2014 to March 2016. The area under the receiver operator characteristics curve (AUC) of PCT for the detection of documented infection (DI) was 0.637, and that of bloodstream infection (BSI) was 0.811. In multivariate analysis, the inability to decrease PCT by more than 80% within 5–7 days from the onset of fever independently predicted poor 100-day survival following allo-HSCT (P=0.036). Furthermore, the prognostic nomogram combining PCTc and clinical parameters showed a stable predictive performance, supported by C-index of 0.808 and AUC of 0.813 in the primary cohort, and a C-index of 0.691 and AUC of 0.697 in the validation cohort. This study demonstrated the diagnostic role of PCT in documented and bloodstream infection during the neutropenic period after allo-HSCT. PCTc might serve as a predictive indicator of post-HSCT 100-day mortality. The nomogram based on PCTc and several clinical factors effectively predicted the 100-day survival of febrile patients and may help physicians identify high-risk patients in the post-HSCT neutropenic period.